Feline Coronavirus Type II Strains 79-1683 and 79-1146 Originate from a Double Recombination between Feline Coronavirus Type I and Canine Coronavirus - Herrewegh, Arnold A. P. M. (American Society for Microbiology, 1998)
Recent evidence suggests that the type II feline coronavirus (FCoV) strains 79-1146 and 79-1683 have arisen from a homologous RNA recombination event between FCoV type I and canine coronavirus (CCV). In both cases, the template switch apparently took place between the S and M genes, giving rise to recombinant viruses which encode a CCV-like S protein and the M, N, 7a, and 7b proteins of FCoV type I (K. Motowaka, T. Hoh- datsu, H. Hashimoto, and H. Koyama, Microbiol. Immunol. 40:425–433, 1996; H. Vennema, A. Poland, K. Floyd Hawkins, and N. C. Pedersen, Feline Pract. 23:40–44, 1995). In the present study, we have looked for additional FCoV-CCV recombination sites. Four regions in the pol gene were selected for comparative sequence analysis of the type II FCoV strains 79-1683 and 79-1146, the type I FCoV strains TN406 and UCD1, the CCV strain K378, and the TGEV strain Purdue. Our data show that the type II FCoVs have arisen from double recombination events: additional crossover sites were mapped in the ORF1ab frameshifting region of strain 79-1683 and in the 5′ half of ORF1b of strain 79-1146.